Addressing Challenges in Humanistic Communication During COVID-19 Through Medical Education - Amin, Shefali; Chin, Justin; Terrell, Mark A.; Lomiguen, Christine M. (Frontiers in Communication, 2021)
The current global pandemic due to COVID-19 has resulted in widespread lockdowns, social distancing, and other protective guidelines; these infectious control and mitigation measures challenge the medical system and create anxiety amongst all populations. In hospitals and healthcare facilities, patient interaction and shared decision making are sacrificed for fear of COVID-19 nosocomial spread. The intangible effects of human interaction with COVID-19 patients, whether it be a physician or a patient’s family, are replaced with isolation amid ventilators. Medical professionals must find a way to practice life-saving medical care while maintaining humanistic and professional interactions. This research provides insight into the necessity and challenges of humanistic communication during COVID-19 across various institutions and offers short-term solutions and reforms through medical education.